Measles vaccination programme in Sarawak - an evaluation of service provision and uptake / Chai Phing Tze - Chai, Phing Tze (2016)
Since 2009, Malaysia has maintained 95% coverage of its national measles vaccination programme as recommended by the World Health Organization, and is now moving towards measles elimination. However, in 2011, Malaysia suffered a nationwide outbreak of measles. This study explored the underlying causes of the 2011 measles outbreak by looking into both user and provider perspectives of the vaccination service. This was a mixed mode study which comprised secondary data analysis, in-depth interviews and operations research. It examined the association between immunization received at inappropriate age and occurrence of measles outbreak, in addition to current evidence to determine the relevance of current age recommendation for measles vaccine. The Malaysian World Health Survey 2002 dataset was examined to determine the performance of the national immunisation programme and proposed new indicators for age-appropriate vaccination. This was followed by an operations research on the management of the immunization service, cold chain integrity, as well as providers’ knowledge and practices. Lastly the experience, needs and barriers faced by non-vaccinating parents in accessing measles vaccination service were explored using qualitative in-depth interview. Delays in obtaining measles vaccine among infants increase both risk and magnitude of measles outbreak. In Malaysia, age-appropriate measles vaccine coverage was 50%, hitherto undetected due to lack of monitoring, and could have contributed to the 2004 and 2011 outbreaks. Serosurveys conducted over the past decade showed waning of maternal antibody during infancy as early as three months old, especially among children born to vaccinated mothers and premature infants. Intervention studies suggested that infants responded well to early vaccination at six months old. Twelve non-vaccinating parents from Sarawak were successfully traced and interviewed. Parents revealed they faced multiple challenges in immunizing their children. Decision on vaccination was found to be the interaction between a parent’s iv experience with illnesses, relationship with health workers, social network, personal belief system, material circumstances and structural barriers. During the operations research 102 clinics in Sarawak were surveyed. Knowledge and practice of vaccine storage and management by health providers were found to be inadequate, further reducing the accessibility and efficacy of vaccination service. Age-recommendation for measles vaccine should be lowered to protect higher proportion of young infants. Age-appropriate vaccination indicators more accurately reflect the population susceptibility to measles and should be routinely reported. A central infant vaccination database is indicated to facilitate tracing of defaulters, and to monitor performance of vaccination service. Improving health providers’ responsiveness to parents and transforming the socio-economic landscape will remove barriers to quality vaccination service for poor parents. Designing locally relevant strategies to promote vaccine acceptability would improve uptake among the hesitant parents.